1988
DOI: 10.1139/g88-112
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic mutants in potato, Solanum tuberosum L. I. Expression and identity of genes for desynapsis

Abstract: For tuber-bearing Solanum species, six monogenic recessive synaptic mutants, designated sy-1, sy-2, sy-3, sy-4, ds, and dsc have been reported in the literature. In the present investigation no indication for the existence of the mutant sy-1, affecting megasporogenesis only, was found. The mutant ds was confirmed to display typical desynaptic behaviour in microsporogenesis and shown to similarly affect megasporogenesis. It furthermore proved to be allelic to the mutants sy-3 and dsc. It is proposed that the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 13 publications
1
36
0
Order By: Relevance
“…In the cultivated potato (Solanum tuberosum) and related diploid Solanum species, meiotic restitution appears to be associated with asynapsis and desynapsis [129,175], abnormal spindle orientation at the second division [175][176][177], and abnormal cytokinesis [177]. A number of monogenic meiotic mutants that produce 2n pollen or 2n eggs in potato have been reported, including parallel spindles (ps), premature cytokinesis-1 (pc-1) and premature cytokinesis-2 (pc-2) [178], desynaptic (ds-1) and synaptic mutants (sy-1, sy-2, sy-3, and sy-4) [179], and omission of the second division (os) [180]. Different genetic systems for meiotic restitution were also observed in soybean [166,168,[181][182][183][184].…”
Section: Meiotic Restitution and Polyploidiza-tionmentioning
confidence: 99%
“…In the cultivated potato (Solanum tuberosum) and related diploid Solanum species, meiotic restitution appears to be associated with asynapsis and desynapsis [129,175], abnormal spindle orientation at the second division [175][176][177], and abnormal cytokinesis [177]. A number of monogenic meiotic mutants that produce 2n pollen or 2n eggs in potato have been reported, including parallel spindles (ps), premature cytokinesis-1 (pc-1) and premature cytokinesis-2 (pc-2) [178], desynaptic (ds-1) and synaptic mutants (sy-1, sy-2, sy-3, and sy-4) [179], and omission of the second division (os) [180]. Different genetic systems for meiotic restitution were also observed in soybean [166,168,[181][182][183][184].…”
Section: Meiotic Restitution and Polyploidiza-tionmentioning
confidence: 99%
“…Wagenvoort et al, 1990Lelley et al, 1987Ramanna, 1983Iwanaga, 1984;Werner & Peloquin, 1987;Jongedijk & Ramanna, 1988;Watanabe & Peloquin, 1993Parrott & Smith, 1984Rabe & Haufler, 1992Vorsa, 1986in Ortiz et al, 1992Nassar, 1992Simpson & Davis, 1983 Werner & Peloquin, 1991a Mok & Peloquin, 1975 Stelly & Peloquin, 1986;Watanabe & Peloquin, 1989;Werner & Peloquin, 1987;Zhang et al, 1988Vorsa, 1986in Ortiz et al, 1992Werner & Peloquin, 1987Sala et al, 1989Zhang et al, 1988Nassar, 1992Ray & Tokach, 1992Mok & Peloquin, 1975Ramanna, 1978;Camadro & Peloquin, 1980;Iwanaga & Peloquin, 1982;Watanabe & Peloquin, 1989;Masuelli et al, 1992 Jones, 1990Orjeda et al, 1990Zhang et al, 1988Vorsa & Bingham, 1979Bingham & McCoy, 1979;Tavoletti et al, 1991aMyers et al, 1984Parrott & Smith, 1984Werner & Peloquin, 1991aRay & Tokach, 1992Werner & Peloquin, 1987Wagenvoort et al, 1990…”
Section: Cytological Aspects Of 2n Gamete Productionmentioning
confidence: 99%
“…Later, Nel (1975) found that this el allele is responsible for both the FDR and SDR modes of 2n egg formation. In Solanum tuberosum (Veilleux, 1985) an abnormal synapsis of homologous chromosomes was once thought to be controlled by six monogenic recessives, but it is now considered to be under monogenic control (dsl) with several alleles, probably acting in conjunction with one or two other genes that remain to be clearly identified (Jongedijk & Ramanna, 1988). In Solanum, premature cytokinesis appears to be controlled by recessive alleles at two independent loci (pel and pc2) (Mok & Peloquin,\97Sb).…”
Section: The Genetic Basis Of 2n Gamete Productionmentioning
confidence: 99%
“…The IPCR derived fragments were used for RFLP analysis in a segregating diploid potato population termed CxE (Jongedijk and Ramanna, 1988; J.M.E. Jacobs, unpublished) along with a set of tomato DNA probes mapped in potato (Bonierbale et al, 1988).…”
Section: Methodsmentioning
confidence: 99%